The Effect of Certified Teacher Ability in Improving the Learning Ability of Grade V Students of SD Negeri Wayura - Nggego, Friskianto; B.M. Gagaramusu, Yusdin; Firmansyah, Arif (CV Kalimasada Group, 2024)
This study aims to determine the impact of certified teacher ability on the improvement of learning abilities of fifth-grade students at SD Negeri Wayura. This is a quantitative study using a survey method. The study was conducted in the fifth grade of SD Negeri Wayura. The sample size for this study is 10, comprising 9 students and 1 teacher. The data collection technique used in this study was a questionnaire. The results of the first hypothesis test with a partial test (T-test) showed T calculated = -2.444 > T table = 2.365 with a significance of 0.045 < 0.05, indicating that Ho is rejected and Ha is accepted. Based on the explanation above, it can be concluded that there is an influence of certified teacher competence on the improvement of the learning abilities of fifth-grade students at SD Negeri Wayura. Furthermore, the results of the second test, which is the coefficient of determination (R Square), is 0.678 (67.8%). This figure means that the influence of certified teacher competence on the improvement of students' learning abilities is 67.8%. Based on the analysis conducted, it can be concluded that there is an influence of certified teacher competence on the improvement of the learning abilities of fifth-grade students at SD Negeri Wayura.